2023
DOI: 10.3389/fsurg.2023.1156489
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and clinical outcomes of operatively treated patients with flail chest injuries: A multicentre prospective cohort study

Abstract: IntroductionMost studies about rib fractures focus on mortality and morbidity. Literature is scarce on long term and quality of life (QoL) outcomes. Therefore, we report QoL and long-term outcomes after rib fixation in flail chest patients.MethodsA prospective cohort study of clinical flail chest patients admitted to six level 1 trauma centres in the Netherlands and Switzerland between January 2018 and March 2021. Outcomes included in-hospital outcomes and long-term outcomes, such as QoL measurements 12 months… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…50 They so far published four relevant papers with a natural experiment as methodology and more studies are being conducted and soon to be published. 27,28,51,52 One study showed that with a natural experiment design on rib fixation there was no difference in outcome between nonoperative and operative treated patients. 27 The inclusion was finished one year earlier than predicted and took three years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 They so far published four relevant papers with a natural experiment as methodology and more studies are being conducted and soon to be published. 27,28,51,52 One study showed that with a natural experiment design on rib fixation there was no difference in outcome between nonoperative and operative treated patients. 27 The inclusion was finished one year earlier than predicted and took three years.…”
Section: Discussionmentioning
confidence: 99%
“…21 Multiple natural experiments in trauma surgery have been conducted reporting results matching the credibility of randomized controlled trials. [24][25][26][27][28] However, natural experiment design is a relatively new study method in surgical research. This is also the case in spinal trauma and it is currently unknown to what degree natural experiment designs are utilized and to what extent they provide credible evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Severe pain can worsen breathing difficulties. Flail chest is the second most common cause of death from chest trauma after chest vascular injury ( 3 ). Open reduction and internal fixation (ORIF) of ribs is often used to resolve the instability of the chest wall in patients with flail chest ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%